Auditory cortex: representation through sparsification? - Willmore, B; King, A (2009)
The recent discovery of combination-sensitive neurons in the primary auditory cortex of awake marmosets may reconcile previous, apparently contradictory, findings that cortical neurons produce strong, sustained responses, but also represent stimuli sparsely. © 2009 Elsevier Ltd. All rights reserved.